Pengaruh Tingkat Penerapan Teknologi Pengendalian Hama Terpadu (Pht) Terhadap Petani Padi Sawah - Noviza Fitri; Helvi Yanfika; Indah Istiana; Serly Silviyanti Soepratikno (Politeknik Negeri Lampung, 2022)
This study aimed to analyze the effect of application level of Integrated Pest Management (IPM) technology on Paddy Rice Farmers. The research was carried out in October - November 2021 in Metro City. The sample was 25 farmers selected by purposive technique. Data analysis were descriptive statistics and correlation. Inferential statistical analysis obtained by Spearman Rank correlation test. The results of the analysis showed that the relationship between individual characteristics and the level of application of IPM technology was obtained by sig. 0.000 (99% confidence level). The conclusion was that there was a strong relationship between individual characteristics and the level of application of IPM technology. The results of the analysis of the relationship between the application of the basic principles of IPM with the level of application of IPM technology obtained a sig value. 0.083 (90% confidence level). The conclusion was that there was a sufficient relationship between the application of the basic principles of IPM and the level of application of IPM technology.